How to make the Lunar and Martian soils suitable for food production - Assessing the changes after manure addition and implications for plant growth. (1st January 2023) - Caporale, Antonio G.; Palladino, Mario; De Pascale, Stefania; Duri, Luigi G.; Rouphael, Youssef; Adamo, Paola
Abstract: The in-situ resource utilisation (ISRU), in terms of native rocky materials and astronaut wastes, is crucial in contests of soil-based space-farming. Nevertheless, extra-terrestrial soils are very different from Earth soils, lacking any form of organic carbon and associated macro and micronutrients. In this research, we aimed to study and modify two commercially available Lunar and Martian regolith simulants (LHS-1 from Exolith Lab and MMS-1 from Martian Garden) to make them an adequate medium for plant growth. Lettuce was chosen as reference crop to guide the discussion on the results obtained. To reach this main objective, we added to simulants a commercially available monogastric-based organic manure chosen as a substitute of a possible organic amendment produced onboard. The simulant/manure mixture rates were 100:0, 90:10, 70:30, 50:50; w:w. As expected, an approximately linear increase of total and bioavailable contents of macro (N, S, P, Ca, K, Mg) and micro (Fe, Mn, Cu, Zn) nutrients with increasing manure addition to simulants was observed. On the other hand, the very high pH of manure (pH, 9.02) along with its salinity (EC, 6.7 dS m −1 ) and sodicity (Na, 5.3 g kg −1 ), did not correct the already high pH of simulants (very high for LHS-1), but rather raised their soluble salt content and sodium amount on the exchange complex. In addition, an increase of toxic soluble aluminium and heavy elements (Pb, Ni, Cr, V) was observed, mainly in the strongly alkaline lunar simulant/manure mixtures. The addition of an organic source also produced a generalised improvement of water retention and hydraulic conductivity of both regolith simulants, in proportion to the percentage of manure addiction. For both situations, the best mixture ratio was 70:30. In terms of water retained, the LHS-1 mixtures benefited more than the MMS-1 ones by manure addition since water was held more in the "dry" (between −100 and −600 cm of matric potential head) than in the "humid" (between −25 and −100 cm of matric potential head) region of water retention. This would make LHS-1 mixtures more useful for cultivation of lettuce, at least in terms of physico-hydraulic properties. Nevertheless, the overall characterisation of the mixtures unveiled that MMS-1-based substrates can ensure better agronomic performances than LHS-1 ones, mainly due to lower pHs and higher nutrient availability; this divergent fertility was particularly evident at 90:10 simulant/manure rate and tend to be mitigated by increasing the levels of manure. Highlights: Lunar LHS-1 and Martian MMS-1 simulants lack vital nutrients and physical structure. Horse/swine manure is an analogue of a possible organic amendment produced in BLSS. Manure amendment improved chemical fertility of simulants and nutrient availability. Physico-hydraulic properties of two simulants were enhanced by organic fertilisation. 70:30 simulant/manure mixture was the best in terms of fertility and sustainability.